Efficacy of Nintedanib for Idiopathic Pulmonary Fibrosis and Its Safety for Breastfeeding and Pregnancy - Santoso, Resyana; Yoki Citra Perwira; Stevia Ariella Pasande (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background : An interstitial lung disease called pulmonary fibrosis can cause breathing difficulties by leaving scars in the lungs. IPF is the most prevalent kind of PF. A multiple tyrosine kinase inhibitor called nintedanib received approval for use in antifibrotic treatment. There are two dosage forms for nintedanib: 100 mg and 150 mg for oral use. Two times a day, 150 mg should be taken with food. The FVC decrease was effectively reduced with nintedanib. In INPULSIS-1, INPULSIS-2, and a data set , the yearly rate of FVC decrease was considerably reduced in nintedanib users than in placebo users. The mortality rate from respiratory causes was 3.8% for patient received nintedanib as opposed to 5.0% for patient received placebo. In this review, we mainly reviewed reports on efficacy of nintedanib for IPF and its safety for breastfeeding and pregnancy. Method : This review extracted the resources from PubMed using the boolean method [â€Efficacy of nintedanibâ€ OR "nintedanib efficacyâ€] AND "pulmonary fibrosisâ€. Compared to people who used placebo in the INPULSIS-1 and INPULSIS-2 trials, nintedanib recipients showed significantly decreased annual rates of FVC. Before beginning nintedanib and as needed throughout treatment, confirm your pregnancy status. Women should be informed that breastfeeding is not advised due to the possibility of harmful side effects in nursing babies from nintedanib. Conclusion, patients treated with nintedanib observed a decreased rate of Interstitial Lung Disease development compared to who treated with placebo and it's not recommended for pregnant and breastfeeding women. latarbelakang: Penyakit paru interstisial yang disebut fibrosis paru dapat menyebabkan kesulitan bernapas dengan meninggalkan bekas luka di paru-paru. Fibrosis paru idiopatik merupakan jenis fibrosis paru yang paling banyak. Nintedanib merupakan inhibitor tirosin kinase yang digunakan dalam pengobatan antifibrotic. Ada dua bentuk sediaan nintedanib untuk dikonsumsi secara oral : 100 mg dan 150 mg. Dosis 150 mg dikonsumsi dua kali sehari bersama dengan makanan. Penggunaan nintedanib sangat efektif dalam penurunan Forced Vital Capacity(FVC) dalam INPULSIS-1, INPULSIS-2, dan kumpulan data, tingkat penurunan Forced Vital Capatcity(FVC) tahunan sangat berkurang pada pengguna nintedanib daripada pengguna plasebo. Tingkat kematian akibat penyebab pernapasan adalah 3,8% untuk pasien yang menerima nintedanib dibandingkan dengan 5,0% untuk pasien yang menerima plasebo. Dalam ulasan ini, kami meninjau laporan tentang kemanjuran nintedanib untuk fibrosis paru idiopatik  dan keamanannya untuk menyusui dan kehamilan. Metode: Ulasan ini mengambil sumber dari PubMed menggunakan metode boolean ["Efikasi nintedanib" ATAU "kemanjuran nintedanib"] DAN "fibrosis paru". Dibandingkan dengan orang yang menggunakan plasebo dalam uji coba INPULSIS-1 dan INPULSIS-2, penerima nintedanib menunjukkan tingkat Forced Vital Capacity (FVC) tahunan yang menurun secara signifikan. Sebelum memulai nintedanib dan sesuai kebutuhan selama perawatan, konfirmasikan status kehamilan Anda.